Plasmodium falciparum Secretome in Erythrocyte and Beyond - Soni, Rani; Sharma, Drista; Bhatt, Tarun K. (Frontiers in Microbiology, 2016)
Plasmodium falciparum is the causative agent of deadly malaria disease. It is an intracellular eukaryote and completes its multi-stage life cycle spanning the two hosts viz, mosquito and human. In order to habituate within host environment, parasite conform several strategies to evade host immune responses such as surface antigen polymorphism or modulation of host immune system and it is mediated by secretion of proteins from parasite to the host erythrocyte and beyond, collectively known as, malaria secretome. In this review, we will discuss about the deployment of parasitic secretory protein in mechanism implicated for immune evasion, protein trafficking, providing virulence, changing permeability and cyto-adherence of infected erythrocyte. We will be covering the possibilities of developing malaria secretome as a drug/vaccine target. This gathered information will be worthwhile in depicting a well-organized picture for host-pathogen interplay during the malaria infection and may also provide some clues for development of novel anti-malarial therapies.